Effectiveness of RFID and cloud computing on precast logistic management and precast prefinished volumetric construction module tracking - Ng, Bao Yong (Nanyang Technological University, 2022)
Singapore’s construction industry has seen improvement in productivity over the past decade. Despite facing daunting pressures from the momentous global pandemic, which led to labour shortages and rising material costs, the construction industry is expected to grow steadily. The productivity improvement is made possible with the government efforts in research and development (R&D) to replace traditional construction methods and technology integration to digitalise manual processes. The Precast Prefinished Volumetric Construction (PPVC) method was introduced to reduce construction time and the number of workers at the site.